Analisis Pengaruh Non Performing Financing (NPF), Earnings Asset Quality (KAP), Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Operational Efficiency Ratio (BOPO) terhadap Tingkat Profibilitas pada Bank Muamalat Indonesia Tahun 2017-2023 - Arif Rahman Siregar; Nurlaila Nurlaila; Nurul Jannah (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze and explain the effect of non-performing financing, quality of earning assets, capital adequacy, financing to deposit ratio (FDR), and BOPO on the level of profitability of Bank Muamalat Indonesia in 2017-2023. The research data used is secondary data from the annual report of Bank Muamalat Indonesia. The research method used is quantitative which is carried out systematically, specifically, and structurally. The data analysis technique used in this study is the Multicollinearity Test, F Test, t Test, and Multiple Linear Regression Analysis to determine the effect of each variable on the level of profitability. The results of this study indicate that partially the KAP, NPF, FDR, BOPO, ROA variables have a significant and simultaneous effect on the variable level of profitability.